Prevalence of hypertension and microalbuminuria in children of hypertensive and non-hypertensive parents in Calabar, Nigeria: A comparative study - Akpakpan IV; Ineji EO; Anah MU; Ikpeme OE; Amajor AC; Uzomba CI (Ibom Medical Journal)
Background: High blood pressure (HBP) and microalbuminuria are common in children of parents with hypertension. Microalbuminuria is a strong predictor of early stage hypertension as well as kidney injury.